The IHO ECDIS Colours and Symbols - Eaton, Mike (The International Hydrographic Review, 2001)
The IHO Colours and Symbols for ECDIS aim to provide a clear, unambiguous and accurate presentation of the chart on the ECDIS display, and to ensure that the mariner has the means of selecting the chart information he needs with nothing superfluous, to avoid clutter. This paper describes what the IHO Specifications do, outlines how they evolved, lists some of the guiding principles used, and describes current controversies and some future considerations.